The Learning Curve in Skullbase Surgery Part 2–From the Microsurgical Lab Training to the Operative Room - Isolan, Gustavo Rassier; Monteiro, Jander; Vaz, Marco Antônio Schlindwein; Lavinsky, Joel; Araújo, Ricardo Lopes de; Figueiredo, Eberval Gadelha; Bark, Samir Aler; Polanski, José Fernando; Ribas Filho, Carmem Austrália Paredes; Ribas Filho, Jurandir Marcondes; Malafaia, Osvaldo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
In this second part, the authors review and suggest a methodology for studies in skull base surgery and training in microsurgical laboratory, based on their experiences and reflections. Not only are the foundations for the acquisition of microsurgical skills presented, but also what is needed to be an effective skullbase surgeon with good results. The present article reflects in particular the philosophy of professor Evandro de Oliveira and also serves to present to the neurosurgical community a new state-of-the-art laboratory for hands-on courses in Brazil, at the Faculdade Evangélica Mackenzie do Paraná.
Keywords: skullbase; learning curve; microsurgical laboratory